2011
DOI: 10.1016/j.bbr.2011.07.045
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal-prefrontal dynamics in spatial working memory: Interactions and independent parallel processing

Abstract: Memory processes may be independent, compete, operate in parallel, or interact. In accordance with this view, behavioral studies suggest that the hippocampus (HPC) and prefrontal cortex (PFC) may act as an integrated circuit during performance of tasks that require working memory over longer delays, whereas during short delays the HPC and PFC may operate in parallel or have completely dissociable functions. In the present investigation we tested rats in a spatial delayed non-match to sample working memory task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(87 citation statements)
references
References 55 publications
4
82
1
Order By: Relevance
“…This hypothesis seems to be supported by a previous study, which showed that the intermediate CA1 region of the hippocampus and the medial prefrontal cortex interact in coordinating RM and PM processes in anticipation of obtaining a remote goal [67]. Earlier neurocognitive studies suggested that dopaminergic modulation of hippocampal-prefrontal cortical interaction plays a key role in PM.…”
Section: Discussionsupporting
confidence: 55%
“…This hypothesis seems to be supported by a previous study, which showed that the intermediate CA1 region of the hippocampus and the medial prefrontal cortex interact in coordinating RM and PM processes in anticipation of obtaining a remote goal [67]. Earlier neurocognitive studies suggested that dopaminergic modulation of hippocampal-prefrontal cortical interaction plays a key role in PM.…”
Section: Discussionsupporting
confidence: 55%
“…Recent evidence suggests that these structures mutually interact to process memory/working memory (WM). For instance, it has been shown that inactivation of either structure, or their disconnection, impairs spatial working memory (Floresco et al, 1997; Lee and Kesner, 2003; Yoon et al, 2008; Churchwell et al, 2010; Churchwell and Kesner, 2011; Griffin, 2015). In addition, the two structures show coherent activity during the performance of certain working memory tasks (Jones and Wilson, 2005; Colgin, 2011; Gordon, 2011; O'Neill et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This function would be important for maintaining goal-directed behavior over time to meet one's needs, so it could be considered important in governing sustained attention. Finally, the lateral regions appear to be important in providing emotional tone during memory EVALUATING VENTRAL-MEDIAL SYSTEM ATTENTION encoding and retrieval (e.g., orbital-hippocampus; Churchwell & Kesner, 2011;Hoover & Vertes, 2011). With evidence suggesting memory function is impaired during excessive or minimal emotional states as discussed earlier, this function could influence how individuals acquire and use memory in adaptive ways for goal-directed behavior (Young & Shapiro, 2011).…”
Section: Moving Beyond the Cortico-centric ''Cool'' Dorsal And ''Hot'mentioning
confidence: 96%